OPTIMIZATION OF BACTERIAL CELLULOSE PRODUCTION FROM SUGAR BEET MOLASSES BY GLUCONACETOBACTER XYLINUS NRRL B-759 IN STATIC CULTURE - Oz, Yunus Emre; Kalender, Mehmet (Editura Acad Romane, 2021)
We investigated the optimization of bacterial cellulose (BC) production from sugar beet molasses by Gluconacetobacter xylinus NRRL B-759 in static culture. The optimization studies were performed using the central composite design (CCD) of response surface methodology (RSM). The independent variables were the molasses concentration, inoculation ratio and culture volume. The dependent variable was BC production yield. From the optimization tests, based on the model developed by RSM-ANOVA, it was found that binary interactions between molasses concentration-culture volume and inoculation ratio-culture volume had the most significant influence on the responses. The optimum conditions were as follows: 78.932 g/L molasses concentration, 12.973% inoculation ratio, and 130.405 mL of culture volume. The obtained BC was characterized by Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM) and elemental analysis. The characterization results obtained in the study revealed that the produced BC exhibited typical FTIR spectrum, elemental composition, and nanofiber structure.
Keywords: bacterial cellulose; sugar beet molasses; Gluconacetobacter xylinus NRRL B-759; optimization; static culture